Glance at the chemodiversity of Ocimum species: Trends, implications, and strategies for the quality and yield improvement of essential oil - Gurav, Tanuja P.; Dholakia, Bhushan B.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Ocimum species represent commercially important medicinal and aromatic plants. The essential oil biosynthesized by Ocimum species is enriched with specialized metabolites specifically, terpenoids and phenylpropanoids. Interestingly, various Ocimum species are known to exhibit diverse chemical profiles, and this chemical diversity has been at the center of many studies to identify commercially important chemotypes. Here, we present various chemotypes from the Ocimum species and emphasize trends, implications, and strategies for the quality and yield improvement of essential oil. Globally, many Ocimum species have been analyzed for their essential oil composition in over 50 countries. Asia represents the highest number of chemotypes, followed by Africa, South America, and Europe. Ocimum basilicum L. has been the most widespread and well-studied species, followed by O. gratissimum L., O. tenuiflorum L., O. canum Sims, O. americanum and O. kilimandscharicum Gurke. Moreover, various molecular reasons, benefits, adverse health effects and mechanisms behind this vast chemodiversity have been discussed. Different strategies of plant breeding, metabolic engineering, transgenic, and tissue-culture, along with anatomical modifications, are surveyed to enhance specific chemotypic profiles and essential oil yield in numerous Ocimum species. Consequently, chemical characterization of the essential oil obtained from Ocimum species has become indispensable for its proper utilization. The present chemodiversity knowledge from Ocimum species will help to exploit various applications in the industrial, agriculture, biopharmaceutical, and food sectors.
Keywords: Chemodiversity; Chemotype; Essential oil; Metabolic engineering; Ocimum; Specialized metabolites